Indore city bus transport service (A) - Raghuram, G., 1955- (SAGE Knowledge. Cases., 2010)
Towards the end of the 1990s, mounting losses forced the Madhya Pradesh State Road Transport Corporation (MPSRTC), the sole provider of public transport in the central Indian state of Madhya Pradesh, to suspend its urban transport services. As a consequence, organized public transport services ceased to exist in Indore, the largest metropolitan city in the state. This void was soon filled by the Intermediate Public Transport System (IPTS), consisting of minibuses, tempos and auto rickshaws. In January 2004, 300 private minibuses, 150 tempos and 10,000 auto rickshaws were plying in the city under the IPTS.According to policy makers and city administrators, lack of public transport (PT) was one of the key reasons for the sharp increase in personalized vehicles on the roads, leading to an alarming increase in pollution levels and in the number of road accidents. Worried over the deteriorating condition of the city, they made several attempts to revive the public transport system, but these were unsuccessful for a variety of reasons.Then, in November 2005, the Collector and District Magistrate of Indore, Vivek Aggarwal, decided to make another attempt to revive the city's public transport system. This attempt was conceived as a public-private partnership (PPP). The two cases, Indore City Transport Service (A) and Indore City Transport Service (B), discuss the complexity involved in planning, rolling out and running a public transport service in Indore on a sustainable basis.Case (A) details the prevalent socioeconomic conditions and travel characteristics of Indore and the positions taken by various stakeholders with regard to providing a public transport service in the city. The readers/ participants have to conceptualize a transport system for the city, and, taking the role of Aggarwal, they must prepare a concept note for the state cabinet's approval.